2023
DOI: 10.1039/d2dt03760b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the nuclearity of [Mo2O2S2]2+-based assemblies by playing with the degree of flexibility of bis-thiosemicarbazone ligands

Abstract: The [MoV2O2S2]2+-based thiosemicarbazone complexes appear as very promising molecules for biological applications due to the intrinsic properties of their components. This paper deals with the synthesis and the characterization of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(124 reference statements)
0
3
0
3
Order By: Relevance
“…40 In our recent work, we reported the synthesis and characterization of bis-thiosemicarbazone-based [Mo V 2 O 2 S 2 ] 2+ complexes containing flexible or rigid (only aromatic) spacers between the two thiosemicarbazone units. 41 Replacing the central aromatic ring by a phenol leads to bis-thiosemicarbazone ligands well suited to form di-copper(II) complexes. 34,36,39,40,[42][43][44] In this context, the aim of this study is to develop a new series of dicopper(II) complexes and investigate their antioxidant, antifungal and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…40 In our recent work, we reported the synthesis and characterization of bis-thiosemicarbazone-based [Mo V 2 O 2 S 2 ] 2+ complexes containing flexible or rigid (only aromatic) spacers between the two thiosemicarbazone units. 41 Replacing the central aromatic ring by a phenol leads to bis-thiosemicarbazone ligands well suited to form di-copper(II) complexes. 34,36,39,40,[42][43][44] In this context, the aim of this study is to develop a new series of dicopper(II) complexes and investigate their antioxidant, antifungal and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…De obicei, din structura metaloproteinelor se observă că atomul central este coordinat prin intermediul atomilor de sulf, oxigen și azot [2,7]. Acest set de atomi se întălnește și la tiosemicarbazone -o clasă de compuși organici, cu interes științific ridicat în ultimele două decenii [8][9][10][11][12]. Datorită proprietăților sale biologice tiosemicarbazone tind să-și găsească utilizare în calitate de agenții: anticancer, antivirali, antibiotice, antitumorale, antimalerice, antioxidative și antifungice [6][7][8][9][10][11][12][13].…”
Section: Introducereunclassified
“…Acest set de atomi se întălnește și la tiosemicarbazone -o clasă de compuși organici, cu interes științific ridicat în ultimele două decenii [8][9][10][11][12]. Datorită proprietăților sale biologice tiosemicarbazone tind să-și găsească utilizare în calitate de agenții: anticancer, antivirali, antibiotice, antitumorale, antimalerice, antioxidative și antifungice [6][7][8][9][10][11][12][13]. Structura chimică a tiosemicarbazonelor determină capabilitatea de formare Seria ,,Ştiinţe reale și ale naturii" Științe chimice ISSN 1814-3237 a compușilor coordinativi, unde tiosemicarbazonele servesc în calitate de liganzi polidentați, prin intermediul atomilor de azot, sulf și în unele cazuri oxigen [8][9][10].…”
Section: Introducereunclassified
See 1 more Smart Citation
“…In another study, cuboidal trinuclear and tetranuclear metal−chalcogenido clusters were shown to be efficient optical limiters [ 18 ]. Studies of molybdenum cluster compounds are not limited to the above complexes and applications and concern clusters of different nuclearity and structure [ 4 , 19 , 20 , 21 , 22 , 23 ]. However, there is much less work demonstrating their properties and potential applications.…”
Section: Introductionmentioning
confidence: 99%